1997
DOI: 10.1002/(sici)1097-0185(199703)247:3<317::aid-ar3>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Liver of the brown trout, Salmo trutta (Teleostei, Salmonidae): A stereological study at light and electron microscopic levels

Abstract: Background: A quantitative study was undertaken for the first time on the normal liver of male and female 2-year-old brown trout, Salmo trutta.Methods: Liver was fixed by controlled perfusion. Organ-level morphometry provided weight and volume. A two-stage stereological approach was performed at light and electron microscopy levels. Systematic sampling and point-counting morphometry were used for estimating the relative volumes of the structural compartments. Total absolute volumes of these components were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 0 publications
6
35
0
2
Order By: Relevance
“…Teleosts do not appear to have a canal of Hering, but instead the canaliculi empty directly into the lumen of preductules, which are formed by biliary pre-ductal epithelial cells (PDEC), a specialized cell of the intrahepatic biliary tree in teleosts (Hinton and Pool, 1976;Rocha et al, 1994). PDECs form the lumen of the pre-ductule by wrapping around themselves, analogous to capillary formation by endothelial cells (Hinton and Couch, 1998;Hinton and Pool, 1976;Rocha et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teleosts do not appear to have a canal of Hering, but instead the canaliculi empty directly into the lumen of preductules, which are formed by biliary pre-ductal epithelial cells (PDEC), a specialized cell of the intrahepatic biliary tree in teleosts (Hinton and Pool, 1976;Rocha et al, 1994). PDECs form the lumen of the pre-ductule by wrapping around themselves, analogous to capillary formation by endothelial cells (Hinton and Couch, 1998;Hinton and Pool, 1976;Rocha et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…This provides the opportunity to carry out an embryonic screen to identify mutants that are defective in either liver development or function, or both. Third, baring minor differences, the anatomy, function, organization and cellular composition of adult zebrafish and mammalian livers are virtually the same (Hinton and Couch, 1998;Rocha et al, 1994;Wallace and Pack, 2003), as is the histopathology of fatty liver (steatosis), cholestasis and neoplasia (Amatruda et al, 2002;Spitsbergen et al, 2000) (J. Glickman, personal communication), allowing direct comparison between zebrafish and mammalian liver disease processes. Indeed, recent work has demonstrated that genes that underlie Alagille Syndrome, a pediatric disorder that results in a paucity of intrahepatic bile ducts, among other defects, play an important role in zebrafish biliary development .…”
Section: Introductionmentioning
confidence: 99%
“…It is considered a target organ for the study of interactions among environmental factors and structure and/or hepatic functions (Bruslé & Anadon). In this sense, the morphological characteristics of the liver have been associated with physiological status in fish (Caballero et al, 1999) and used as an indicator of environmental quality (Rocha et al, 1994;Al-Youseif et al, 2000;Gochfeld, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The diffuse to radial arrangement has been reported in other teleosts [9,22]. This diffuse arrangement may help in the rate of liver functions especially that of detoxification and metabolite storage, as more cells will be reached faster in an aquatic environment that ingestion of food and water is very frequent.…”
Section: Discussionmentioning
confidence: 59%